RELATIONSHIP OF ADENOSINE DEAMINASE AND SERUM FERRITIN LEVELS WITH BODY MASS INDEX IN CHILDREN. A CROSS-SECTIONAL STUDY. - Sirvi, Gautam Chand; Nama, Mayank; Purohit, Abhinav; Suman, Shubhendu Kumar (Student's Journal of Health Research Africa, 2023)
Objectives: The study aims to establish the correlation between serum adenosine deaminase and ferritin levels with somatometric measurements in children aged 6 to 14. Additionally, it sought to assess the association of these biochemical parameters with components of dysmetabolic syndrome, including blood pressure and lipid profile. Methods: The multicentric study, conducted over 2 years from Jan 2021 to Dec 2022 at a tertiary care center, focused on children aged 6 to 14 attending the outpatient department for eyesight irregularities or immunization. A total of 120 children meeting specific inclusion criteria underwent meticulous anthropometric measurements, BMI calculation, and comprehensive biochemical assessments to correlate serum adenosine deaminase (ADA) as well as ferritin levels with various parameters. The biochemistry tests were performed at the Department of Biochemistry, Nalanda Medical College & Hospital, Patna. Results: In the study of 120 children (6-14 years), the overweight/obese group (n=60) showed higher weight (52.309 kg) compared to the normal weight group (n=60, 27.945 kg). Anthropometric measures, excluding common parameters, were significantly elevated in the obese cohort. Robust positive correlations were noted amongst systolic blood pressure, adenosine deaminase, and serum ferritin with BMI, and significant associations were noted between anthropometric measures and ferritin levels, with ADA showing significance only in systolic blood pressure and waist-hip ratio. Conclusion: The current study revealed significant associations between anthropometric measures, serum adenosine deaminase (ADA), and ferritin levels in children aged 6-14. These findings emphasize the interplay between obesity, inflammatory markers, and cardiovascular health in this pediatric population. Recommendation: The study recommends further research with larger samples to validate findings and emphasizes the importance of longitudinal studies to elucidate dynamic relationships between anthropometric measures, inflammatory markers, and metabolic outcomes in paediatric populations.